Kelayakan donor darah pada mahasiswa di Kota Semarang - Adita Puspitasari Swastya Putri; Dina Afrianti (Jurnal SAGO Gizi dan Kesehatan, 2022)
Background: Public awareness of donating blood has been increasing. However, in reality, many prospective donors still do not fulfill the predetermined blood donation requirements. Donors must first undergo a medical examination, measuring blood pressure, blood type, and hemoglobin (Hb) levels, and medical consultation. The eligibility to become a blood donor can then be determined.Objectives: This study aims to determine the eligibility of blood donors based on laboratory examination among university students in Semarang City.Methods: An observational study using a cross-sectional design was conducted at the Central Java Provincial Health Laboratory Center in June 2022. Data collection through laboratory and medical examinations includes preliminary examination (blood type and rhesus examination), hemoglobin and hematocrit examination, and medical examination (body weight, blood pressure, pulse, and body temperature). Data processing was done in stages: editing, coding, entry, and cleaning data. Data analysis was only done descriptively, including frequency distribution and percentage. Data were presented in the form of graphs and tables.Results: More donors were female students (80%), and 100% had positive rhesus. Laboratory examination results showed normal hemoglobin levels (76,7%) and normal hematocrit (95,0%), and standard pulse rate (71,7%). The feasibility of blood donation by students is feasible (43,3%) and not feasible (56,7%).Conclusion: The general health condition of students showed an optimal level of health for blood donation; however, many students in Semarang are not eligible to donate blood.